PENGARUH.BUDAYA.ORGANISASI,.MOTIVASI.KERJA.DAN.DISIPLIN.KERJA iTERHADAP.KINERJA.KARYAWAN.PADA.PDAM iKABUPATEN iNGANJUK - Mubarokah, Lisa Fitri; Wihara, Dhiyan Septa; Suprajitno, Edy Djoko (Universitas Nusantara PGRI Kediri, 2022)
Organizational culture is something that affects all components of the organization, determines its identity, and can be used by members of the organization to guide their behavior. This study has a purpose, namely to determine the correlation between organizational culture, work motivation, and work discipline on the performance of PDAM Nganjuk Regency employees. The type of quantitative research is the type of research used and the method used is the main data collection method. The main data obtained from the questionnaire. The number of samples used in this study were 40 employees of PDAM Nganjuk Regency using non-probability sampling. The analysis of this research was conducted using SPSS IBM 23 software. This study used data analysis techniques in the form of classical assumption test, multiple linear regression analysis, coefficient of determination, t test, and F test. The results of this study indicate that organizational culture and work motivation variables do not has a significant effect on the performance of some employees, while work discipline has a significant effect on employee performance. Organizational culture, work motivation, and work discipline all have a significant effect on employee performance productivity.